Microbial degradation of Diquat by strain Meyerozyma guilliermondii Wyslmt: Identification of transformation products and clarification of degradation pathways - Wang, Fangyuan; Jia, Jinrong; Gu, Wei (Frontiers in Microbiology, 2025)
The continuous and extensive use of pesticides has negative impacts on the environment and human health. Microbial remediation is an eco-friendly and economically efficient technology, which is of great significance. In this investigation, the degradation of the herbicide Diquat by yeast Wyslmt was studied in medium under different conditions. The degradation rate of Diquat showed a pattern of first increasing and then decreasing with the increase of the inoculation amount of Wyslmt, temperature, pH and the initial concentration of Diquat. The biodegradation transformation products (BTPs) formed by the microbial degradation of Diquat in the culture medium solution were isolated and identified by ultra-high-performance liquid chromatography coupled with time-of-fight mass spectrometry (UPLC-QTOF-MS). Based on the mass spectrometry information, three main transformation products were determined. The calculation of components, the comparison of structural analogues, and the existing literature are all helpful for the determination of the structure. The main pathway of microbial degradation was C–C bond broken, hydroxylation and demethylation. These results lay the foundation for further environmental risk assessment and provide a reference for the bioremediation evaluation of bipyridine herbicides.